Clinical characteristics and prognostic analysis of CDKN2A/2B gene in pediatric acute lymphoblastic leukemia: a retrospective case-control study - Shi-Mei Huang; Hui-Qin Chen; Li-Ting Liu; Ya-Ting Zhang; Jian Wang; Dun-Hua Zhou; Jian-Pei Fang; Lu-Hong Xu (Hematology)
In this retrospective case-control study involving 424 pediatric patients diagnosed with Pediatric Acute Lymphoblastic Leukemia (ALL), the investigation focused on analyzing the clinical characteristics and prognosis associated with the Cyclin-dependent kinase inhibitor 2A/2B (CDKN2A/2B) gene. Treatment and evaluation followed the South China Children's Leukemia Group-ALL-2016 protocol (SCCLG-ALL-2016). Among the cohort, 92 patients (21.7%) exhibited CDKN2A/2B gene deletions, with 11.1% homozygous and 10.6% heterozygous deletions. Notably, ALL patients that do have CDKN2A/2B gene deletions tended to present at an older age (P = 0.001), demonstrate hepatosplenomegaly on palpation (P < 0.001), and exhibit a higher incidence of Central nervous system leukemia (CNSL) (P = 0.037) and T-ALL (P = 0.007). A significant correlation was observed between ALL that does have CDKN2A/2B gene deletions and ETV6::RUNX1-positive (8.7% vs. 19.3%, P = 0.017) and IKZF1 gene deletions (20.7% vs. 8.4%, P = 0.001). Survival analysis of 392 patients revealed no significant differences in 5-year relapse, Overall survival (OS), or Event-free survival (EFS) between ALL that does/ does not have CDKN2A/2B gene deletions. Subgroup analysis highlighted poorer prognosis among hepatosplenomegaly patients in the CDKN2A/2B gene deletion group, with a 5-year EFS of 81.8%, 95%CI (0.695–0.963), P = 0.05. Hepatosplenomegaly emerged as the most significant prognostic factor for EFS [HR = 2.306, 95%CI (1.192–4.461), P = 0.013]. Cox regression analyses identified covariates influencing prognosis, ALL with the CDKN2A/2B gene showing no significant impact on outcomes. In conclusion, while ALL that does have CDKN2A/2B gene deletions is associated with certain clinical characteristics and genetic aberrations, they did not significantly impact OS or EFS. Furthermore, subgroup analysis revealed a potential prognostic role of ALL that does have CDKN2A/2B deletions presenting with hepatosplenomegaly on palpation, emphasizing the importance of comprehensive risk stratification in treatment decision-making for this subgroup.